A facile synthesis of a ZIF-derived ZnS/ZnIn2S4 heterojunction and enhanced photocatalytic hydrogen evolution. Issue 31 (23rd July 2020) - Song, Huihui; Wang, Na; Meng, Hao; Han, Yide; Wu, Junbiao; Xu, Junli; Xu, Yan; Zhang, Xia; Sun, Ting
Abstract : A novel heterostructure of ZIF-derived ZnS/ZnIn2 S4 is formed by nano-ZnS uniformly dispersed in ZnIn2 S4 flower, which displays enhanced photocatalytic reactions. Abstract : A facile synthetic route, by using rhombic dodecahedral zeolitic imidazolate framework-8 (ZIF-8) as the structure template, is devoted to fabricating the ZnS/ZnIn2 S4 hybrid heterojunction; the compact heterostructure was produced by combining the sulfurization of ZIF-8 and the in situ precipitation of ZnIn2 S4 in one pot. The resulting ZnS nanoparticles of about 100 nm were uniformly dispersed in the folds of flower-like ZnIn2 S4, whose structure is beneficial for charge transfer at the heterointerface. The additional quantities of ZIF-8 are varied to find an optimum ratio of the two components to obtain the best photocatalytic activity. In the photocatalytic hydrogen generation irradiated by simulated solar light, all the ZnS/ZnIn2 S4 hybrid photocatalysts displayed improved hydrogen production rates compared to single ZnS or ZnIn2 S4, and the best hydrogen production rate of 453.4 μmol h −1 g −1 is obtained by ZnS/ZIS-20, whose value is approximately 4 times higher than that of single ZnIn2 S4 . The electrochemical properties of the ZnS/ZnIn2 S4 hybrid photocatalysts were measured to explore the charge transfer mode at the interface, and the band structure and enhanced photocatalytic hydrogen generation mechanism have been proposed. The excellent recycling properties of hydrogen production indicated the prospective applications of this kind of ZIF-derived metal sulfide in photocatalytic reactions.